IMPACT OF ASHWAGANDHA (WITHANIA SOMNIFERA) ON MENTAL HEALTH PROFILE OF ELDERLY WOMEN - Chauhan, Komal; Patil, Gauri. (European Scientific Journal, ESJ, 2013)
Growing old certainly involves a variety of life stressors that can lead to depression at any age, any gender, race or class. Depression is a pervasive and impairing illness affecting women twice more than men. An ayurvedic approach of using herbs like Ashwagandha with its active principle component withanolides seems to be more acceptable to relieve anxiety, stress, depression, aging, fatigue and depressed immunity. About 15 moderately depressed women of 60 years and above age were supplemented 500 mg Ashwagandha tablets per day for 6 weeks. Mental health was assessed by GDI, MMSE and CIT scales. Socio economic status, dietary pattern, health profile and activity pattern were also assessed. After the intervention there was a significant (p ≤0.05) change in number of moderately depressed subjects (base line: 56 percent, final: 13 percent). About 13 percent subjects scored normal MMSE. A significant (p ≤0.05) reduction i.e. 6.3% in CIT score was observed (base line: 14.5, final: 8.2). About 53 percent subjects were showing high self esteem and 93 percent subjects (p=≤ 0.05) were able to meet >50 percent of RDA for major nutrients like energy and protein (base line: 60 percent). Nutrients contributing mental health like tryptophan, methionine, choline, vitamin C and folic acid intake were also improved among 70 percent subjects. Present study showed the beneficial effect of Ashwagandha on moderately depressed elderly women.